Investigation of position estimation accuracy of celestial objects on the CCD frames - Безкровный, Михаил Михайлович; Саваневич, Вадим Евгеньевич; Соковикова, Наталья Сергеевна; Мовсесян, Яна Самвеловна; Погорелов, Артём Витальевич; Дашкова, Анна Николаевна; Дихтярь, Николай Юрьевич; Брюховецкий, Александр Борисович; Михайлова, Любовь Олеговна (Eastern-European Journal of Enterprise Technologies, 2014)
High position estimation accuracy of objects is needed for better detection of celestial objects with nonzero apparent motion, and further clarification of the motion parameters of objects by a small number of measurements. However, the studies of the accuracy of currently used methods for position estimation of objects at the moment have not been carried out. The estimation accuracy of equatorial coordinates of thirty most productive observatories in the world was investigated in the paper. The analysis was conducted by comparing the estimates with their predicted values, obtained on the Minor Planet Center website. Mean values of residuals by right ascension and declination, estimates of the standard deviations of the position estimates of objects, the average module of the measurement residual were calculated for each observatory. The study has shown a significant advantage of observatories, which use CoLiTec software for processing the observation results. According to the average module of residuals and standard deviation in pixels, CoLiTec observatories-partners have taken a leading position among the small aperture telescopes. High measurement accuracy indexes were obtained using sub-pixel Gaussian model.